Influência do jasmonato de metila e do tween 20 na fisiologia e na severidade da ferrugem asiática na soja - Oliveira, Tássia Boeno de (2014)
The Asian soybean rust, caused by the Phakopsora pachyrhizi fungus, is a destructive foliar disease in almost all soy producing countries. In the attempt of mellowing the impacts caused by this disease, this study aimed at evaluating the effect of methyl jasmonate on the induction of resistance to Asian soybean rust through the severity of the disease and the temporal analysis of the chitinase and β-1,3-glucanase enzymes’ activities, as well as the qualitative and quantitative profiles of the phenolic compounds and gas exchange involved. Soy plants of the BRS 361 cultivar, in the V 5 stage, were sprayed with water, 0.02% Tween 20 and methyl jasmonate 1.25 mM in greenhouse. Twenty four hours after spraying, the plants were inoculated with 1.4x10 5 uredospores/mL of Phakopsora pachyrhizi, applying water to the witness plants. With the results obtained we may verify that the methyl jasmonate and Tween 20 were effective in promoting the reduction of disease severity. The application of methyl jasmonate increased the activity of chitinase and β-1,3-glucanase in leaves submitted or not to inoculation, regardless of the evaluation period. The compounds daidzein, daidzin, malonyl daidzin and coumestrol were produced only by plants sprayed with water (false-inoculated). Tween 20 and methyl jasmonate induced the accumulation of these phenolic compounds even in the plants not inoculated. The application of these products also promoted accumulation of other phenolic compounds. The inoculation promoted photosynthetic efficiency reduction expressed by the reduction of ecophysiological characteristics. The application of methyl jasmonate Tween 20 intensified the negative effect of inoculation in stomatal conductance and in transpiration, however, without altering photosynthesis. We conclude that methyl jasmonate and Tween 20 may be considered as Asian soybean rust resistance inducing compounds.